0

solve y+1 / 2 - 2y-1 / 3 = 4

A. y = 29

B. y = -29

C. y = -19

D. y = 19

**Comments**

0

(y+1)/2 - (2y - 1)/3 = 4

Find the LCM of the denominator.

LCM of 2 and 3 is 6

multiply through by 6

6(y + 1)/2 - 6(2y - 1)/3 = 24

3(y + 1) - 2(2y - 1) = 24

3y + 3 - 4y + 2 = 24

3y - 4y + 3 + 2 = 24

-y + 5 = 24

Subtract 5 from both sides

-y = 24 - 5

-y = 19

Multiply both sides by -1

y = -19

**Ans C**

I dont get the first part,after multiplying through 6

2 likes, 0 dislikes

How did you multiple by 6

2 likes, 0 dislikes

Your Answer